A capacity model based on charging process for state of health estimation of lithium ion batteries. (1st September 2016) - Li, Xue; Jiang, Jiuchun; Wang, Le Yi; Chen, Dafen; Zhang, Yanru; Zhang, Caiping
Highlights: A capacity model based on charging process is proposed to estimate SOH. The accuracy of the model is validated on commercial lithium ion batteries. The universality of the model is verified on different batteries and statuses. Abstract: The incremental capacity (IC) analysis method is widely used to analyze the aging origins and state of health (SOH) of lithium ion batteries. This paper analyzes the technical difficulties during the application of the IC analysis method at first. A universal capacity model based on charging curve is then proposed, which not only inherits the advantages of IC analysis method but also avoids the tedious data preprocessing procedure, to estimate SOH of lithium ion batteries. The feasibility and accuracy of the model are demonstrated. To verify the accuracy and flexibility of the proposed capacity model, it is applied on different types of lithium ion batteries including LiFePO 4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2, and Li 4 / 3 Ti 5 / 3 O 4 . Furthermore, the proposed capacity model is applied on the aged cells to validate the model accuracy during the whole life span of lithium ion batteries. The results show that the model error is less than 4% of the nominal capacity for each case.